As motivações invisíveis da emigração dekassegui ao Japão - Ocada, Fábio Kazuo [UNESP] (My University, 2011)
Among the wide contexture defined by the international migration intensified in the last decades of the 20th century and the rouse debate over the generalization of these precarious working conditions, the main objective of this study being here presented is to formulate an understanding of the composed historical reasons that lead the Nikkei Brazilian workers to departure to their ancestors homeland and the main purpose is to disclose the reason why these Nikkei Brazilian workers accept the unqualified jobs, that can be definied by the trinomial: dirty, dangerous and heavy.

Em meio ao amplo contexto definido pelas migrações internacionais que se intensificaram nas últimas décadas do século XX; e ao debate suscitado pela generalização destas condições precarizadas de trabalho, a formulação de um entendimento das motivações historicamente constituídas, que norteiam a partida de trabalhadores nikkei-brasileiros à terra de seus antepassados, constitui o eixo central do estudo que aqui se apresenta, tendo por objetivo desvendar o sentido causal da aceitação dos postos desqualificados de trabalho, definidos pelo trinômio sujo, perigoso e pesado.